2002
DOI: 10.1097/00125817-200205000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Spina bifida and folate-related genes: A study of gene-gene interactions

Abstract: Purpose: To assess whether interactions of common alleles of two folate genes contribute to spina bifida risk.Methods: Case-control study, comparing 203 children with spina bifida to 583 controls. Results: Homozygosity for the 677C-T allele of 5,10-methylenetetrahydrofolate reductase (MTHFR) alone was associated with an odds ratio for spina bifida of 1.57 (95% confidence interval [CI], 1.02-2.38). For the 844ins68 allele of cystathionine-␤-synthase alone, the odds ratio was 0.83 (95% CI, 0.39 -1.64). For the j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 45 publications
3
8
0
Order By: Relevance
“…A similar gene-gene interaction has been reported in NTD-affected cases [de Franchis et al, 2002], suggesting that interactions between variant alleles of CBS and MTHFR genes can be an etiologic factor shared by these two common midline defects.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A similar gene-gene interaction has been reported in NTD-affected cases [de Franchis et al, 2002], suggesting that interactions between variant alleles of CBS and MTHFR genes can be an etiologic factor shared by these two common midline defects.…”
Section: Discussionsupporting
confidence: 67%
“…However, the co-occurrence of this allele with the c.677T allele of the MTHFR c.677C > T polymorphism has been associated with a significant increase in the risk for arterial and venous occlusive disease [de Franchis et al, 2000], and, in some studies, for spina bifida [de Franchis et al, 2002]. Specifically, although data from individual studies vary, the combined evidence [Ramsbottom et al, 1997;Speer et al, 1999;de Franchis et al, 2002] suggests an increased frequency of c.677TT homozygosity combined with c.844ins68 heterozygosity among neural tube defects (NTDs) patients compared to controls (data summarized in de Franchis et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…CBS rs5742905 has not been examined previously in relation to SB. The most common CBS mutation studied is the 844ins68 allele, 11 bp downstream of rs5745905, which has shown varied association with NTDs or SB in different ethnic populations 28, 33, 34. Supporting this finding the CBS 844ins68 allele has been associated with lower serum homocysteine in a recent population study of over 10,000 subjects in Norway 35…”
Section: Commentmentioning
confidence: 83%
“…Further experiments are needed to determine if the rs3737965 variant directly affects MTHFR transcription or is linked with a disease causing allele in our SB patients. Other studies have noted gene-gene interactions in various SNP alleles of MTHFR 28, 34, 41. All of these studies identified risk related to C677T.…”
Section: Commentmentioning
confidence: 99%
“…Mutations of the CBS gene, such as the 844ins68 allele, have been described (Sebastio et al, 1995). There have been conflicting studies regarding the potential interaction among alleles of different folate-related genes, such as the 677C-T allele of the methylene tetrahydrofolate reductase ( MTHFR ) gene and the 844ins68 allele of CBS , and their combined contribution to risk of SB (Ramsbottom et al, 1997; Speer et al, 1999; de Franchis et al, 2002; Houcher et al, 2009). …”
Section: Introductionmentioning
confidence: 99%